Subdivision Depth Computation for Tensor Product n-Ary Volumetric Models - Ghulam Mustafa; Muhammad Sadiq Hashmi (Abstract and Applied Analysis)
We offer computational formula of subdivision depth for tensor product n-ary (n⩾2) volumetric models based on error bound evaluation technique. This formula provides and error control tool in subdivision schemes over regular hexahedron lattice in higher-dimensional spaces. Moreover, the error bounds of Mustafa et al. (2006) are special cases of our bounds.